Double-layer Compliant Intermittent Mechanism for Single-drive Electric Opening Latch Safety Branch Chain - Xiaojie Huang; Lubin Hang; Qiansheng Wang; Xiaobo Huang; Mingyuan Wang (Jixie chuandong)
To realize electric opening and electric lock with a single-motor drive in vehicle door latch，a double-layer compliant intermittent mechanism that can cooperate the movement of electric opening and electric safety branch chains is constructed，based on the characteristic that the elastic force of the constant force spring does not change with the change of the stroke. The forward driving pin-unit is supported by a lever support rigidized driving pin to move the type face turntable disk. The reverse driving pin-unit，the driving pin is disengaged from the support-level by the resistance of the turntable disk torsion spring，the driving pin rotates around the center and slides on the surface of the turntable disk. The mechanism has multiple movement modes including initial-support-maintenance，rigid-support-driving and compliant-avoidance adapted to the disk profile. Multi-mode switching of double-layer compliant intermittent mechanism can be realized by clockwise and anticlockwise rotation. The mechanism is simulated in the narrow space of the door latch，to realize the definite and reset movement of electric opening and lock mechanism under multi-working conditions. Comparing the contact force between the driving pin and the turntable disk，the maximum value is smaller and the change range is stable when using constant force spring，which realizes adaptability with other branch chains. The results show that，the mechanism can realize unlock in 30.8 ms，sequence unlock and electric opening in 97 ms，independent lock can be realized in 68.9 ms.